2014
DOI: 10.1186/1471-2474-15-31
|View full text |Cite
|
Sign up to set email alerts
|

Acute murine antigen-induced arthritis is not affected by disruption of osteoblastic glucocorticoid signalling

Abstract: BackgroundThe role of endogenous glucocorticoids (GC) in the initiation and maintenance of rheumatoid arthritis (RA) remains unclear. We demonstrated previously that disruption of GC signalling in osteoblasts results in a profound attenuation of K/BxN serum-induced arthritis, a mouse model of RA. To determine whether or not the modulation of the inflammatory response by osteoblasts involves T cells, we studied the effects of disrupted osteoblastic GC-signalling in the T cell-dependent model of antigen-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Interestingly, disruption of endogenous glucocorticoid signaling in chondrocytes appears to have the opposite effect on inflammatory arthritis compared to that mediated by osteoblasts. In addition, our previous study showed that murine AIA is not affected by disruption of glucocorticoid signaling in osteoblasts (8), while in the current study, chondrocytes appear to regulate inflammation in the AIA model through endogenous glucocorticoid signaling. The differential modulations of immune arthritis by osteoblasts and chondrocytes can be due to the distinct soluble factors secreted by these 2 cell types.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Interestingly, disruption of endogenous glucocorticoid signaling in chondrocytes appears to have the opposite effect on inflammatory arthritis compared to that mediated by osteoblasts. In addition, our previous study showed that murine AIA is not affected by disruption of glucocorticoid signaling in osteoblasts (8), while in the current study, chondrocytes appear to regulate inflammation in the AIA model through endogenous glucocorticoid signaling. The differential modulations of immune arthritis by osteoblasts and chondrocytes can be due to the distinct soluble factors secreted by these 2 cell types.…”
Section: Discussioncontrasting
confidence: 43%
“…AIA was initiated in both WT and chGRKO mice as previously described (8,12). Eight-week-old chGRKO mice and their WT littermates were immunized by subcutaneous injection of 100 mg methylated bovine serum albumin (mBSA; Sigma-Aldrich) dissolved in 50 ml PBS and emulsified in 50 ml Freund complete adjuvant (Sigma-Aldrich) into both flanks (50 mg each) on d 21.…”
Section: Antigen-induced Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…The regions of interest of femoral cancellous bone were chosen for analysis. With use of the cross-sectional images from micro-CT scanning, longitudinal analysis of the distal femur excluding the cortical bone was performed in the measurement area between 1 and 4 mm distal to the growth plate-metaphysis junction [10,18]. Bone volume/total volume (BV/TV), structure model index (SMI), trabecular number (Tb.N), trabecular separation (Tb.Sp), trabecular thickness (Tb.Th), and connectivity density (Conn.D) at the left distal femur were measured.…”
Section: Micro Computer Tomography Examinationmentioning
confidence: 99%
“…In 2014, the same group reported that acute murine antigeneinduced arthritis, a T-celledependent arthritis model, is not affected by disruption of osteoblastic endogenous GC signaling. 9 These data indicate that osteoblasts do not modulate the T-cellemediated response via an endogenous GC-dependent pathway.…”
Section: Osteoblasts Modulate the Innate Immune Responsementioning
confidence: 88%